Vengeance Is God’s: Jesus’s Perpetuation of Jewish Teachings - Langer, Ruth (Studies in Christian-Jewish Relations, 2026)
Negative stereotypes of the “vengeful Jew” draw on language found in Matthew’s presentation of the Sermon on the Mount. This essay argues that this antisemitic stereotype results from an uncritical reading of Matthew. It derives from the particular format into which Matthew casts the contrasts in what are often called his “antitheses.” In contrast, both Paul and Luke show continuity with the Jewish biblical tradition which understands divine vengeance to be an expression of God’s ensuring justice in the world, suggesting that this was likely Jesus’s own understanding. This essay also surveys the consequences of the Matthean stereotype on Christian thinking about Jews, contrasting this with actual Jewish prayers for divine vengeance.